Implementation of Criminal Case Trials Through a Teleconference by Prosecutors with a Progressive Legal Approach - Muhamad Mahrus Setia Wijaksana (Faculty of Law, Universitas Sebelas Maret, 2020)
The development of technology in the era of the 4.0 industrial Revolution, characterized by digitalization until covering the realm of criminal law, was affected by the activity of law enforcement. Moreover, this time crowded about criminal trials through teleconference in the middle increasingly the mass of pandemic spread covid-19 which of course also affects the duties and authority of the prosecutor. The study focuses on analyzing the implementation of the trial in a teleconference by prosecutors with a progressive legal approach, highlighting the law as